Design and Simulation Analysis of Marine Wedge Gear Propeller Shaft Clutches - Yu Xiangdong; Yin Haobo; Li Tie; Wu Wei (Jixie chuandong)
Aiming at the problem of parameter design of marine wedge gear propeller shaft clutches, the design and research of marine wedge gear propeller shaft clutches are carried out. The variation of the critical friction coefficient required for the self-locking of the marine wedge gear propeller shaft clutch with the pressure angle and wedge angle of the wedge gear is theoretically analyzed and verified by the simulation. The multi-body dynamic model of marine wedge gear propeller shaft clutches is established, and the engagement process with the tooth error is studied. The results show that the marine wedge gear propeller shaft clutch reduces the accuracy requirement of the tooth alignment process. When there is an error within 0.4° in the engagement process, the engagement can be completed under its own guidance. The formula of self-locking critical friction coefficient derived in this study can be used to guide the design of marine wedge gear propeller shaft clutches.